Ellenberg indicator values for macromycetes – a methodological approach and first applications. (June 2017) - Simmel, Josef; Bässler, Claus; Poschlod, Peter
Abstract: Ellenberg indicator values (EIVs) describe the realized niche of species and habitat parameters, and are commonly used for vascular plants, bryophytes, and lichens. We provide a methodology for EIVs and an EIV list for nearly 650 species of macromycetes. We propose a new EIV scale, namely substrate openness (O). We also give the results of two applications and compare EIV values related to the Red List classification with those related to lifestyle classification. Mycorrhizal species on average have higher demands on substrate openness and are less tolerant of high nutrient levels than saprotrophic or parasitic species. Critically endangered species have on average distinctly higher demands on openness of habitat and substrate than not threatened or less strongly threatened species, which in turn have higher demands for nutrient availability. This pattern clearly highlights the points of threat for many macromycete species. Highlights: Ellenberg indicator values for 636 macromycete species are proposed. Substrate openness is newly introduced as an indicator value. Altogether, values for nine EIV scales were compiled. Ecological needs are compared regarding the species' Red List status and lifestyle.